Tata Susila Sembahyang Umat Hindu - Saputra, I Wayan (Metta : Jurnal Ilmu Multidisiplin, 2022)
The purpose of this research to reveal and find out how the etiquette of prayer for Hindus is, The background of the problem in this article is that there are still many Hindus who still have wrong ethics when praying. This article raises the title of Hindu prayer etiquette (a contemplation). This research is a qualitative research, qualitative research is also called naturalistic research because the research is carried out in natural conditions. The data collection method used is the study of literature, the study of literature is to examine the literature related to this research. Furthermore, the data is processed and presented so as to know how the etiquette of prayer for Hindus is and in this study is a key instrument. The findings in this study are (1) Hindus face the temple of dressing politely and in accordance with applicable rules/norms, (2) the challenges of Hindus when performing sitting prayers according to the standard silasana for men and wajrasana for women, (3) Hindus in positioning their hands when interacting/worshiping must be in accordance with the rules and standards, (4) Hindus should when nunas tirta and bija must comply with literary instructions and when people already know good and perfect attitudes/morals in doing so. worship of course Hindus have to do as what is already known. The purpose of obeying ethics/morals in prayer is nothing but asking for his grace to always be healthy and always in His protection. Thus, he will improve his quality, from the quality of asuri sampad or bad behavior to daiwi sampad or good quality.